Saponins of Dipsacus Azureus Plant and Their Hypocholesterolemic Activity - Аkramov D.Kh; Jabbarov Sh.A; Uljaeva Kh.D; Аshurova L.N (Zien Journals, 2023)
The aerial part of the plant Dipsacus azureus was extracted with 80% ethanol. The extract was concentrated and precipitated with acetone (sum of saponins), and the remaining residue was fractionated into aqueous, n-butanol and chloroform parts. The acetone-precipitated precipitate (sum of saponins) and aqueous fractions were examined for hypocholesterolemic properties.
Keywords: saponins; Dipsacus azureus; hypocholesterolemic activity; extract